2009
DOI: 10.1073/pnas.0903627106
|View full text |Cite
|
Sign up to set email alerts
|

Language regions of brain are operative in color perception

Abstract: The effect of language on the categorical perception of color is stronger for stimuli in the right visual field (RVF) than in the left visual field, but the neural correlates of the behavioral RVF advantage are unknown. Here we present brain activation maps revealing how language is differentially engaged in the discrimination of colored stimuli presented in either visual hemifield. In a rapid, event-related functional MRI study, we measured subjects' brain activity while they performed a visual search task. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 48 publications
6
50
1
Order By: Relevance
“…The categorical response was early in the ERP trace but even earlier (i.e., P1) components have been recently claimed for color categories (Holmes et al, 2009;Thierry et al, 2009). Given the activation of language areas in color judgments, these recent ERP studies suggesting categorical activity in (extra)striate cortical areas would appear to require a rapid activation of feedback networks during color processing (Siok et al, 2009). Presumably, these feedback loops are disrupted by concurrent verbal activity (Gilbert et al, 2006; and hence color perception is no longer categorical Given such clear implication for language in human color CP, we examined the cross-species research that might lead one to believe that non-humans also demonstrate CP for colors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The categorical response was early in the ERP trace but even earlier (i.e., P1) components have been recently claimed for color categories (Holmes et al, 2009;Thierry et al, 2009). Given the activation of language areas in color judgments, these recent ERP studies suggesting categorical activity in (extra)striate cortical areas would appear to require a rapid activation of feedback networks during color processing (Siok et al, 2009). Presumably, these feedback loops are disrupted by concurrent verbal activity (Gilbert et al, 2006; and hence color perception is no longer categorical Given such clear implication for language in human color CP, we examined the cross-species research that might lead one to believe that non-humans also demonstrate CP for colors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite preserved color vision, in addition to a retained ability to categorize other stimuli, patients in these studies failed to understand the meaning of color terms, and failed to sort colors, suggesting that colors do not automatically form categories once color terms have been lost. Further, neuroimaging studies showed left hemisphere activations in known language areas during color comparison tasks (e.g., Siok et al , 2009;Tan et al, 2008;Thierry et al, 2009). For example, in Siok et al (2009) it was only categorical color decisions in a visual search task that were accompanied by activation in language areas.…”
Section: Contrasted Findings On Hemispheric Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, many studies have found that the effect of language on color perception is lateralized to the left hemisphere (Franklin, Drivonikou, Bevis, et al, 2008;Franklin, Drivonikou, Clifford, et al, 2008;Gilbert, Regier, Kay, & Ivry, 2006;Liu et al, 2010;Mo, Xu, Kay, & Tan, 2011;Siok et al, 2009;Tan et al, 2008;Thierry, Athanasopoulos, Wiggett, Dering, & Kuipers, 2009). For instance, Gilbert et al (2006) chose four graduated colors as experimental material, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%